Current knowledge of TNF-α monoclonal antibody infliximab in treating Kawasaki disease: a comprehensive review - Chen, Jiaying; Liao, Jian; Xiang, Lupeng; Zhang, Shilong; Yan, Yajing (Frontiers in Immunology, 2023)
Kawasaki disease (KD), a common autoimmune an autoinflammatory disease primarily affecting young children, characterized by consisting of acute systemic vasculitis and coronary artery involvement in severe cases. Intravenous immunoglobulin gamma (IVIG) combined with aspirin therapy is the first-line regimen for the prevention of coronary aneurysms in the acute phase of KD. The etiology and pathogenesis of KD are unclear, but its incidence is increasing gradually, especially in the cases of IVIG-naïve KD and refractory KD. Conventional therapies for refractory KD have unsatisfactory results. At present, infliximab (IFX), a human-murine chimeric monoclonal antibody that specifically blocks tumor necrosis factor-α (TNF-α), has made great progress in the treatment of KD. This review revealed that IFX infusion (5 mg/kg) could effectively modulate fever, reduce inflammation, improve arthritis, diminish the number of plasma exchange, decrease hospitalizations, and prevent the progression of coronary artery lesions. The adverse effects of IFX administration included skin rash, arthritis, respiratory disease, infusion reaction, hepatomegaly, depressed myocardial contractility, and vaccination-associated complications. But the incidence of these adverse effects is low.The clear optimal application protocol of the application of IFX for either initial combination therapy or salvage therapy in KD is still under investigation. In addition, there are no effective biomarkers to predict IFX resistance. Further multicenter trials with large sample size and long-term follow-up are still needed to validate the clinical efficacy and safety of IFX for IVIG-resistant KD or refractory KD.